The Influence of Price and Instagram Social Media Promotion on Purchase Decisions at Rumangsa Coffee and Bakery, Hotel Ra Premiere Jakarta - RB, Linda Desafitri; Nurbaeti, Nurbaeti; Asmaniati, Fetty; Rachmatullah, Adam; Atmadja, Valencia Andrea (Institut Pariwisata Trisakti, 2023)
This research aims to determine the influence of price and Instagram social media promotion on purchase decisions. The method used in this research is quantitative descriptive with multiple regression analysis using accidental sampling, while data is collected by distributing questionnaires with a Likert scale of 1 to 5. The population is all visitors who come to Rumangsa Coffee and Bakery at Hotel Ra Premiere Jakarta. The sample uses the Slovin formula of 100 respondents. The results of this study show that price and Instagram social media promotion significantly affect purchase decisions. The price variance of coffee in Rumangsa Coffee and Bakery provides a broader option for consumers with different preferences and budgets. It enriches the consumer experience with varying choices of coffee. Rumangsa Coffee and Bakery needs to improve Instagram promotion with exciting content, relevant hashtags, discounts, customer reviews, and promoting events or contests to increase visitors. This research implies that Rumangsa Coffee and Bakery needs to reconsider pricing and improve Instagram promotion to attract more customers and increase sales. This can be achieved by posting engaging content, using relevant hashtags, giving special discounts or promotions, posting customer reviews, and promoting events or contests related to their cafe. Keywords: Price, Instagram Social Media Promotion, Purchase Decision